1,4-Bis(2,2′:6′,2′′-terpyridin-4′-yl)benzene - Fernandes, José A. (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, C(36)H(24)N(6), comprises a whole molecule. Supramolecular interactions between neighbouring molecules are essentially π–π stacking interactions with small interplanar distances [3.5140 (15) and 3.6041 (15) Å]. The central phenylene ring is tilted with respect to the two pyridine substituents, subtending angles of 36.17 (11) and 34.95 (11)°. Three of the peripheral pyridine substituents are almost coplanar with the central pyridines [dihedral angles = 5.10 (12)-8.21 (12)°], but one subtends an angle of 24.86 (12)°.